2007
DOI: 10.1002/ejic.200601016
|View full text |Cite
|
Sign up to set email alerts
|

Tripyrrinatocadmium Complexes: Enforcing Supramolecular Aggregation by a Large Ion

Abstract: A newly developed method for the preparation of free base tripyrrin ligands HTrpy by cyanide‐promoted demetalation of nickel chelates TrpyNiNCO was used in order to explore the chemistry of cadmium tripyrrins TrpyCdX with a variety of anionic co‐ligands X. The introduction of the large CdII ion into the tripyrrin N3 coordination site was accomplished by the use of cadmium acetate as the metal precursor. Ligand exchange experiments using sodium salts of different anions disclose a marked tendency for pentacoord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Structural similarities, however, are found with the cadmium tripyrrins carrying carboxylate coligands. [13] Here it can be observed that in the case of distorted tetragonal-pyramidal coordination, the axial position is significantly closer to the metal atom than the equatorial one. This observation is similar for a dinuclear nickel tripyrrin with a bridging oxalato ligand, too.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Structural similarities, however, are found with the cadmium tripyrrins carrying carboxylate coligands. [13] Here it can be observed that in the case of distorted tetragonal-pyramidal coordination, the axial position is significantly closer to the metal atom than the equatorial one. This observation is similar for a dinuclear nickel tripyrrin with a bridging oxalato ligand, too.…”
Section: Resultsmentioning
confidence: 90%
“…CHN analyses were performed on an Elementar Vario MicroCube instrument. 1 H-, 13 C-and 19 F-NMR spectra were obtained on a Bruker Avance II 300, a Bruker Avance III HD 500 and a Bruker Avance II 600 spectrometer at room temperature. Chemical shifts (δ) are given in ppm relative to TMS and referenced against residual protio solvent resonances.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pincer complexes have been synthesized since the early 1970 s, [1] and new designs (Scheme 1) continue to emerge due to their rich chemistry. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Complexes of pincer ligands have been employed as crystalline switches, as sensors and most commonly as precatalysts for numerous transformations. [17] Pincer systems are ubiquitous due to their relative ease of synthesis, and most of the reported systems are planar, due to the aromatic backbone that is commonly used.…”
Section: Introductionmentioning
confidence: 99%